2017
DOI: 10.1016/j.polymer.2017.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Complex interplay of short- and long-chain branching on thermal and rheological properties of ethylene/α-olefin copolymers made by metallocene catalysts with oscillating ligand structure

Abstract: Unbridged oscillatory metallocenes are prone to produce heterogeneous chain microstructure, for instance, giving rise to elastomeric polypropylene. Here, we use the bis(2phenylindenyl)ZrCl 2 /MAO catalyst system, featuring oscillating ligands, to copolymerize ethylene with several α-olefins. Through investigation of chain microstructure, thermal and rheological properties, we show that the complex behavior of these materials can be justified by considering a catalyst with dual active center having different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Considering the Van Gurp–Palmen plots and moving from the terminal regime, a common feature that could be observed was that both blends developed an inflection point to a minimum, then increased again up to a maximum, and finally decreased as the dynamics reached the glassy regime. This behaviour has been widely reported in copolymers and binary blends [ 39 , 40 ]. Regarding the 80/20 formulation, it can be observed that a shoulder is observed in the |η*| as well as in the G′ curves before reaching the terminal region, which is shifted to lower ω.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Considering the Van Gurp–Palmen plots and moving from the terminal regime, a common feature that could be observed was that both blends developed an inflection point to a minimum, then increased again up to a maximum, and finally decreased as the dynamics reached the glassy regime. This behaviour has been widely reported in copolymers and binary blends [ 39 , 40 ]. Regarding the 80/20 formulation, it can be observed that a shoulder is observed in the |η*| as well as in the G′ curves before reaching the terminal region, which is shifted to lower ω.…”
Section: Resultssupporting
confidence: 71%
“…Such behaviour is often related to composites exhibiting a physically entangled fibrillar network and percolation threshold effect of the second phase, which, in the present study, would have been created by the topological interactions of the long rPET-O microfibrils [ 40 , 43 ]. Based on the conclusions previously reported, the gradual curve step phenomenon observed in the Van Gurp–Palmen plot as the rPET-O content increases must be attributed to the increasing solid-like behaviour of the melt owing to significant changes in the relaxation mechanisms as a function of the developed morphology.…”
Section: Resultsmentioning
confidence: 99%
“…This is however lower than the melting temperature of linear ethylene homopolymers obtained by the traditional Ziegler-Natta catalysts [28]. That's due to the higher comonomer selectivity of metallocene catalysts, which leads to the incorporation of macromers formed by the irreversible spontaneous chain transfer or the chain transfer to monomer reaction even in the absence of any displacement catalysts [6]. By decreasing the reaction temperature, the sharp melting peaks at high temperatures, gradually disappear and new melting endotherms spanning toward lower melting temperatures appear.…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, the application of GPC and NMR techniques for characterizing polyethylene copolymers requires the employment of toxic solvents at high temperatures. Moreover, as these traditional characterization methods cannot directly resolve the presence of long-chain branches, they are frequently combined with other indirect techniques that have more sensitivity to the presence of such branches [6,37]. Despite thermal properties of polyethylene are traditionally used to quantify the lamellae thickness, and consequently, the fraction of short-chain branches, since our proposed mechanism is incapable of forming such short branches, any deviation from the thermal behavior of linear chains produced in the absence of the displacement catalyst can be correlated to the presence of long-chain branches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation